2020
DOI: 10.3390/nu12072139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Combined with a Healthy Diet or Calanus finmarchicus Oil Supplementation on Body Composition and Metabolic Markers—A Pilot Study

Abstract: Aging is accompanied by a progressive decline in muscle mass and an increase in fat mass, which are detrimental changes associated with the development of health conditions such as type-2 diabetes mellitus or chronic low-grade inflammation. Although both exercise as well as nutritional interventions are known to be beneficial in counteracting those age-related changes, data to which extent untrained elderly people may benefit is still sparse. Therefore, a randomized, controlled, 12-week interventional trial wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
(66 reference statements)
2
14
0
Order By: Relevance
“…We also observed a change in body phenotype toward a lower trunk fat mass and higher lean mass in the ET-Calanus group. A similar effect of Calanus oil combined with ET was recently reported by Wasserfurth et al [ 45 ]. In line with this, we also showed a stronger effect of the combined ET-Calanus intervention on leg muscle strength in a previous publication [ 25 ].…”
Section: Discussionsupporting
confidence: 87%
“…We also observed a change in body phenotype toward a lower trunk fat mass and higher lean mass in the ET-Calanus group. A similar effect of Calanus oil combined with ET was recently reported by Wasserfurth et al [ 45 ]. In line with this, we also showed a stronger effect of the combined ET-Calanus intervention on leg muscle strength in a previous publication [ 25 ].…”
Section: Discussionsupporting
confidence: 87%
“…In general, LC n-3 FAs exert anti-obese effects via AMPK-mediated stimulation of fat metabolism (i.e., suppressing lipogenic genes; activating genes that encode mitochondrial and peroxisomal beta-oxidation in both the liver and muscle) As a result, VAT and fat accumulation (and intermediate metabolites) in peripheral tissues are reduced [14]. In a recent study, it was showed that moderate exercise combined with 2 g CO per day (200 mg EPA + DHA/day) has a beneficial effect on reducing fat mass [46]. In line with this, Dad'ová et al (2020) found a reduction in VAT in obese women after an exercise intervention combined with 2.5 g CO per day (230 mg EPA + DHA/day) [47].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism is not clear, but increased adipose tissue lipolysis and/or decreased lipogenesis, as well as increased hepatic drainage of FAs from the abdominal fat stores, are possibilities that could be further investigated. Although clinical studies are sparse, recent studies in elderly untrained overweight participants 110 suggested that a combination of moderate exercise and intake of oil from C. finmarchicus may promote fat loss. It was also shown that wax ester—bound PUFAs from Calanus oil were significantly incorporated into the membranes of red blood cells, thereby increasing the omega-3-index.…”
Section: Treatment Strategiesmentioning
confidence: 99%